mTORC1 loss impairs epidermal adhesion via TGF-b/Rho kinase activation - Georgess, Dan (2017)
Despite its central position in oncogenic intracellular signaling networks, the role of mTORC1 in epithelial development has not been studied extensively in vivo. Here, we have used the epidermis as a model system to elucidate the cellular effects and signaling feedback sequelae of mTORC1 loss of function in epithelial tissue. In mice with conditional epidermal loss of the mTORC1 components Rheb or Rptor, mTORC1 loss of function unexpectedly resulted in a profound skin barrier defect with epidermal abrasions, blistering, and early postnatal lethality, due to a thinned epidermis with decreased desmosomal protein expression and incomplete biochemical differentiation. In mice with mTORC1 loss of function, we found that Rho kinase (ROCK) signaling was constitutively activated, resulting in increased cytoskeletal tension and impaired cell-cell adhesion. Inhibition or silencing of ROCK1 was sufficient to rescue keratinocyte adhesion and biochemical differentiation in these mice. mTORC1 loss of function also resulted in marked feedback upregulation of upstream TGF-β signaling, triggering ROCK activity and its downstream effects on desmosomal gene expression. These findings elucidate a role for mTORC1 in the regulation of epithelial barrier formation, cytoskeletal tension, and cell adhesion, underscoring the complexity of signaling feedback following mTORC1 inhibition.